The Study of Noun Phrase Structure of English Names for Menus in Selected Restaurants and Cafes in Padang Chinese Town, Indonesia - Cindy, Jessica; Marnita, Rina; Ayendi, Ayendi (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2022)
This paper discusses the phrase structure construction of English in the names of foods and drinks on the list of menus sold by some modern restaurants and cafes. The phrase structure analysis is based on Burton's (2013) and Collins's (2000) theories. The function of the head in structure and types of phrases are determined by applying the deletion technique. The research data were collected from lists of menus used in nine Restaurants and cafes in Pondok, a Chinese Town of Padang City. There are 209 food and drink names in the form of noun phrases. The NPs can be categorized into 31 types, ranging from simple to complex constructions. The most common type is Noun + Noun and Adjective + Noun. The NPs are used more for food names than that for drinks'. It is probably due to the wider variety of cooking styles and food ingredients than drinks. A wide variety of NPs used for the menus' names in the observed restaurants indicates the owners' sufficient knowledge of the English language.